Novel CT and scintigraphic findings of bone metastasis from invasive lobular breast cancer. Issue 1 (8th November 2015) - Al‐Ogaili, Zeyad; Troedson, Russell
Abstract: Introduction: The aim of this study is to identify and describe the computed tomography and scintigraphic imaging patterns of osseous metastasis from invasive lobular breast cancer (ILC). Materials and methods: CT and skeletal scintigraphy (SS) studies of 23 patients with diagnosis of ILC and osseous metastasis on their initial presentation were reviewed. Results: Osseous metastases in 14 patients (60.8%) appear as uniform small sclerotic lesions (USSL) on CT scan. The SS in these patients were interpreted as negative for metastasis (either normal or with some equivocal findings not typical for metastasis). Conclusion: Osseous metastasis from ILC can have a characteristic imaging pattern on CT and SS. The pattern of USSL on CT scan with negative SS is highly suggestive of osseous metastasis from ILC.